2019
DOI: 10.15294/jpii.v8i1.15728
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Pre-Service Physics Teachers in Scientific Literacy: Focus on the Competence and Knowledge Aspects

Abstract: The role of scientific and technological knowledge is needed to compete in the era of industrial revolution 4.0. One of the roles of scientific knowledge is by analyzing the scientific literacy ability of pre-service physics teachers. This research aims to find out how far the achievement of scientific literacy possesses by current pre-service physics teachers. The measurement of scientific literacy encompasses two aspects, namely, competence and knowledge aspects. The subjects of this research were thirty pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…This solving step can train indicators of mathematical problemsolving abilities, namely implementing plans and checking again. The third step of the SSCS learning model is the step of formulating a solution (Create), this step directs students to examine the possibilities that have been mentioned whether wrong or right (Pahrudin et al, 2019). The results that have been done will be arranged as attractive as possible in accordance with the wishes of the students.…”
Section: Discussionmentioning
confidence: 99%
“…This solving step can train indicators of mathematical problemsolving abilities, namely implementing plans and checking again. The third step of the SSCS learning model is the step of formulating a solution (Create), this step directs students to examine the possibilities that have been mentioned whether wrong or right (Pahrudin et al, 2019). The results that have been done will be arranged as attractive as possible in accordance with the wishes of the students.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore in ATI model, students will be divided into various random groups which are then given treatment by the teacher. As an increasing students' mathematical creative thinking abilities in the ATI model it refers to the grouping stage of students who are followed up by the treatment given by the teacher (Pahrudin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…students' scientific literacy abilities, as reported by the Program for International Student Assessment. Other studies have also found that prospective science teachers' scientific literacy abilities remain low (Pahrudin et al, 2019;Sartika et al, 2018). Sunarti (2015) reported that prospective science teachers generally can solve scientific literacy items only at a low cognitive level.…”
Section: / 16mentioning
confidence: 98%